Determinants of LDC Exporters' Performance: A Cross-National Study - Dominguez, Luis V.; Sequeira, Carlos G. (Journal of International Business Studies, 1993)
The success of export-led development initiatives in LDCs depends heavily on export diversification. This paper identifies three patterns of performance among Central American firms engaged in non-traditional exports. Each pattern is associated with a distinct strategy: low involvement-low volume-low content, price-cost-volume, and product-service quality oriented. The discussion emphasizes keys to exporter success and priority areas for public policy.